For a Dialogue Between the Teaching of Chemistry and the History and Philosophy of Chemistry: the Case of the Concept of Chemical Element - Mocellin, Ronei C. (2024)
The concept of element is one of the most important concepts in the chemical sciences. It plays a key role to explain the chemical reactions and the basis of the periodic table. It is also central to the modern philosophy of chemistry because of its role in discussions about the nature of the periodic system and natural classes. In the field of chemistry teaching it is a paradigmatic case of alternative conceptions. In general, two definitions of ‘chemical element’ coexist. The first, due to Lavoisier, conceptualizes an ‘element’ in a macroscopic ontology and the second, usually considered the ‘modern’ definition, conceptualizes an element in an ontology of particle. Some authors state that it is time to consider the former conceptualization as merely ‘historical’ and focus teaching on the basis of the most recent definition. The present paper aims to address this problem from a pluralist perspective by highlighting the pedagogical relevance of incorporating historical-philosophical analyses in the explanation of scientific concepts.